Elaboración e implementación del curso virtual de la asignatura de gestión administrativa de compra- venta para el segundo año de bachillerato unificado del colegio nacional “26 de Noviembre” de la ciudad de Zaruma, período 2013 - 2014 - Aguilar Aguilar, Maryuri Rocío (2014)
Focusing on the needs and requirements of educational institutions , the lack of technology to teaching and learning , the need was created to implement a virtual environment to improve and reinforce learning in order that the same be a key support the work of the teacher. In Zone 7 of the province of El Oro, Canton Zaruma , urban parish Zaruma at the National College " November 26 " by the surveys of teachers and students, the necessary information is obtained to detect the need to implement a virtual environment to improve and reinforce learning in the subject of Administrative Management Trading for sophomore year Considering these requirements we proceeded develop didactic planning for the subject because the teacher did not have the same , based on these are designed, developed and implemented this interactive teaching resource which made it available to the teachers and students meeting provide significant support in the learning process in the course of Administrative Management of Purchase and Sale.